Ownership structure influencing the joint determination of dividend, leverage, and cost of capital - Abhinav Kumar Rajverma; Rakesh Arrawatia; Arun Kumar Misra; Abhijeet Chandra (Cogent Economics & Finance, 2019)
The article analyses inter-dependencies between dividend, capital structure, and cost of capital, factoring the ownership structure of listed firms in India, using 3SLS system approach. The study finds that family firms are dominant with concentrated ownership. Dividend, leverage, and average cost of capital are inter-linked. However, family firms pay lower dividends, consistent with family owners extracting rent from external minority shareholders. Additionally, these firms have high leverage and lower cost of capital, suggesting that family control (reputation) provides intangible value to the firms. Ownership structure plays a critical role in understanding the policy decisions in emerging markets.
Keywords: G32; G35; C39; 330; family firms; ownership structure; dividend; leverage; cost of capital; simultaneous equations